THE EFFECT OF THINK PAIR SHARE METHOD TOWARD THE STUDENTS`READING ACHIEVEMENT - Ilham Ilham (Linguistics and ELT Journal, 2015)
This study aims at investigating the effect of Think-Pair-Share Method toward the students’ reading achievement at MA. Darussalam Beremi. The design of this study is true experimental, in which 111 students as the population and through cluster random sampling, 80 students were selected as the sample. After collecting and computing the data, the writer found that the experimental group were more successful than the students of control group. it can be seen from the critical value of t-test equal to 3.86 is higher than the indication of t- table at the significant level of 5% equals to 1.99, and at the significant level of 1% equals to 2.64 then, at the degree of freedom 78 or nearest 80 on the test indication. In fact, the t-test is significant value for both levels. It means, the cooperative learning method is effective toward the student`s reading achievements. The Think-Pair_Share is effective for teaching reading due to the dependence among the students, it triggers the students to be more active, more communicative, and more interactive in teaching and learning process, and also it applies good evaluation process.